Hair Shaft Abnormalities as a Dermoscopic Feature of Mycosis Fungoides: Pilot Results - Magdalena Jasińska; Joanna Czuwara; Nino Lortkipanidze; Agnieszka Michalczyk; Barbara Borkowska; Patrycja Gajda-Mróz; Marta Kurzeja; Małgorzata Olszewska; Lidia Rudnicka; Adriana Rakowska (Adis, Springer Healthcare, 2024)
Abstract Introduction Diagnosis of persistent erythematous, scaly patches, or plaques can be complex since psoriasis (Ps), eczematous dermatitis (ED), and mycosis fungoides (MF) can be considered. Dermoscopy, which is a noninvasive diagnostic tool, is commonly used to examine blood vessels, scales, and background color; however, research on hair shaft evaluation in inflammatory dermatoses remains scarce. The aim of the study was dermoscopic evaluation of hair shafts in skin lesions localized on the non-scalp skin areas in patients diagnosed with MF, Ps, and ED. Methods This was a retrospective evaluation of 55 patients diagnosed with MF, Ps, and ED. Photographic and dermoscopic documentation of these patients and detailed medical history were evaluated. Results A total of 21 patients with MF, 21 patients with Ps, and 13 patients with ED were evaluated. The examination revealed the presence of various abnormalities of hair shafts (e.g., numerous pili torti, single pili torti, 8-shaped hairs, pigtail hairs, broken hairs, hair shafts rapidly tapered over long sections, hair shafts irregular in thickness, angulated hairs, branched hairs, the presence of trichorrhexis nodosa, and monilethrix-like hairs), yellow dots, and black dots. The presence of pili torti was found in 80% of patients with MF, compared with 16% of patients with Ps and 8% of patients with ED (p < 0.005), with multiple pili torti found only in MF patients (67%) (p < 0.005). Statistically significant differences also applied to hair shafts rapidly tapering over long sections and 8-shaped hairs, which occurred only in MF patients (p < 0.005 and p = 0.035, respectively). Conclusions The presence of hair shaft abnormalities such as numerous pili torti, 8-shaped hairs, and hair shafts rapidly tapering over long sections is an important criterion that should be considered in the dermoscopic differentiation of the patchy/plaque mycosis fungoides and inflammatory dermatoses, such as psoriasis and eczematous dermatitis localized on the non-scalp skin areas.